1983
DOI: 10.1017/s0021859600035450
|View full text |Cite
|
Sign up to set email alerts
|

Growth and development of pigs: a reanalysis of the effects of nutrition on body composition

Abstract: SUMMARYSelected data of McMeekan (1940, 1941) were reanalysed to compare the proportions and distribution of tissues, and the weights of some organs, in pigs growing at different growth rates due to differing levels of nutrition. The effects of variation in fat content were excluded, and the distribution of tissues was compared at the same total weight for each tissue, by allometric regressions. Except for components of the head and neck, and the stomach, the results do not support a concept of retardation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The decrease of the lean proportion in the gain (Table 6 ) showed that at low intake levels the pigs have a preference for muscle gain, whereas the proportion of fat tissue gain increases at higher intake levels. This is in agreement with Davies (1983), who reported that pigs at a high feeding level deposited proportionately more fat and less muscle relative to pigs at a low feeding level.…”
Section: Effect Of Energy Intake Between 45 and 85 Kilogramssupporting
confidence: 93%
See 1 more Smart Citation
“…The decrease of the lean proportion in the gain (Table 6 ) showed that at low intake levels the pigs have a preference for muscle gain, whereas the proportion of fat tissue gain increases at higher intake levels. This is in agreement with Davies (1983), who reported that pigs at a high feeding level deposited proportionately more fat and less muscle relative to pigs at a low feeding level.…”
Section: Effect Of Energy Intake Between 45 and 85 Kilogramssupporting
confidence: 93%
“…This was mainly the result of growth of the liver, kidneys, and digestive tract. An increase in the weights of metabolically active organs with increasing feed intake also was reported by Koong et al (1982Koong et al ( , 1983, Davies (1983), Rao and McCracken (1992), and Bikker et al (1995). This effect presumably reflects a functional hypertrophy of the organs in order to process the incremental amounts of feed and illustrates the adaptive capacity of the gilt to nutrient intake.…”
Section: Effect Of Energy Intake Between 45 and 85 Kilogramsmentioning
confidence: 53%
“…A positive relationship between lean content and the ratio of intermuscular to subcutaneous fat has been described (Kempster and Evans, 1979;Davies, 1983;Kouba et al, 1999). According to Kouba et al (1999), a possible explanation is that selection against overall fatness based on backfat thickness is more effective in decreasing subcutaneous fat relative to intermuscular fat and leads, as a result, to little genetic changes in intermuscular fat accumulation.…”
Section: Correlations Between Cia Traitsmentioning
confidence: 99%